(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Over the past several decades, India has witnessed progressive expansion of women protection laws aimed at addressing domestic violence, dowry harassment, sexual abuse, and workplace harassment. While these laws represent crucial milestones in gender justice, a parallel narrative has emerged in public discourse and some academic circles concerning the alleged misuse of these laws for personal vendettas or coercive gain. This article examines the socio-legal impact of alleged misuse of women protection laws on family structure and social harmony in India. The research analyses historical development of these statutes, judicial responses, sociological implications on familial relationships, and broader community level effects. By situating the Indian experience within international perspectives, the article highlights the complex interplay between legal rights and social norms. It finds that although alleged misuse has significant consequences on family cohesion and community trust, the phenomenon is contextualized within systemic legal and societal challenges that require balanced reform. The article concludes with recommendations for policy, law enforcement, and future research.